High spatial resolution and non-destructive evaluation of wood density and microfibril angle by NIR hyperspectral imaging. Issue 5 (August 2017) - Ma, Te; Inagaki, Tetsuya; Tsuchikawa, Satoru
Wood density and microfibril angle are strongly correlated with wood stiffness, shrinkage, and anisotropy. Understanding the spatial distribution of these values is critical for solid timber applications. In this study, near infrared (NIR) hyperspectral imaging was used to evaluate wood density and microfibril angle in a non-destructive, yet effective manner. Briefly, five wood samples collected from both normal and compression parts of two different Cryptomeria japonica trees were analyzed. Partial least squares regression analysis was performed to determine the relationship between X-ray reference data and NIR spectra, and cross-validation (leave-one-out) was used for checking prediction performances. The validation coefficient of determination (r 2 ) between predicted densities by the NIR technique and measured values by SilviScan (X-ray data) was 0.83 with a root mean squared error of cross-validation (RMSECV) of 105.18 kg/m 3 . Regarding microfibril angle, r 2 and RMSECV were 0.77 and 5.36°, respectively. Finally, wood density and microfibril angle were successfully mapped at a high spatial resolution (156 µm) to facilitate the detection of annual growth ring features and evaluation of aspects of heterogeneous wood quality.